Penjerapan Urea dengan Karbon Aktif dari Kayu Bakar - Rahayu, Theresia Evila Purwanti Sri; Amrullah, Shafwan (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2020)
Activated carbon is a universal adsorbent possessing extensive function in human life. Adsorbent has been used in waste effluent treatment to adsorb variety substances mainly in the form of liquid and gas pollutants, odor adsorbent, food preservative, nutrient carrier for plant, and as fuel cell. Adsorbent is become an interest for its highly adsorption capacity due to its abundant pores on its surface resulting wide surface area, its simple manufacturing, its easy finding raw materials-even from waste material, and its relatively low cost of manufacturing. The purpose of this study is to investigate adsorption capacity and urea uptake percentage of activated carbon made from pyrolyzed firewood. The results obtained in this research are activated carbon from pyrolyzed firewood has urea adsorption capacity 0,026 mg urea/g adsorbent at urea concentration of 500 mg/L as high as 479 mg urea/g adsorbent at urea concentration of 50000 mg/L and urea uptake percentage 8,8 % v/v. This result shows that activated carbon from pyrolyzed firewood has capability to adsorb urea molecules form aqueous solution and therefore pyrolyzed firewood can be an alternative of low cost adsorbent for treating wastewater containing urea.